Adenosine Signaling Mediates Osteogenic Differentiation of Human Embryonic Stem Cells on Mineralized Matrices - Rao, Vikram; Shih, Yu-Ru V.; Kang, Heemin; Kabra, Harsha; Varghese, Shyni (Frontiers in Bioengineering and Biotechnology, 2015)
Human embryonic stem cells (hESCs) are attractive cell sources for tissue engineering and regenerative medicine due to their self-renewal and differentiation ability. Design of biomaterials with an intrinsic ability that promotes hESC differentiation to the targeted cell type boasts significant advantages for tissue regeneration. We have previously developed biomineralized calcium-phosphate (CaP) matrices that inherently direct osteogenic differentiation of hESCs without the need of osteogenic-inducing chemicals or growth factors. Here, we show that CaP matrix-driven osteogenic differentiation of hESCs occurs through A2b adenosine receptor (A2bR). The inhibition of the receptor with an A2bR-specific antagonist attenuated mineralized matrix-mediated osteogenic differentiation of hESCs. In addition, when cultured on matrices in an environment deficient of calcium phosphate (CaP) minerals, exogenous adenosine promoted osteogenic differentiation of hESCs, but was attenuated by the inhibition of A2bR. Such synthetic matrices that intrinsically support osteogenic commitment of hESCs are not only beneficial for bone tissue engineering, but can be used as a platform to study the effect of the physical and chemical cues to the extracellular milieu on stem cell commitment. Insights into the cell signaling during matrix-induced differentiation of stem cells will also help define the key processes and enable discovery of new targets that promote differentiation of pluripotent stem cells for bone tissue engineering.